Drug‐induced sleep endoscopy effect on intraoperative decision making in pediatric sleep surgery: A 2‐year follow up. Issue 6 (1st October 2022) - Frederick, Robert M.; Brandt, Josiah; Sheyn, Anthony
Abstract: Objective: To further demonstrate sleep endoscopy's utility in improving surgical outcomes for pediatric OSA. Methods: This is a retrospective review of surgically naïve patients <18 years old with diagnosed moderate–severe OSA who underwent DISE at the time of initial sleep surgery. Patients included in final analysis had both preoperative and postoperative polysomnograms. Surgical success was defined as an oAHI decrease by at least one diagnostic category. Residual OSA was defined as any patient with postoperative oAHI >1. Results: A total of 106 patients had preoperative and postoperative polysomnograms. Patients with comorbidities comprised 53.8% of the group. Average BMI% was 88.2, with 75.5% classified as obese. The most common area of collapse was the base of tongue, occurring in 32.1% of patients. There was a statistically significant decrease from the mean preoperative oAHI of 29.7 to the mean postoperative oAHI of 6.6 ( p  < 0.001). Surgical success occurred in 76.4% of patients. A postoperative oAHI of <5 was achieved in 57.7% of patients with moderate or severe OSA. The average BMI% of patients who met surgical success was 86.4, while the average BMI% of patients who did not was 90.8. A postoperative oAHI of <5 was achieved in 68.4% of patients with a BMI% < 85, compared with 55.2% of patients with a BMI% ≥ 85. Conclusion: This study supports the utilization of DISE during initial surgery for severe sleep apnea in the pediatric population. It was found to effectively aid in significantly reducing surgically naïve patients' mean oAHI. Level of Evidence: Level III.